KAJIAN PENGARUH SITU TERHADAP RESPON HIDROLOGI DI DAS PESANGGRAHAN MENGGUNAKAN MODEL HEC-HMS - Selamet Kusdaryanto; Dwi Putro Tejo Baskoro; Suria Darma Tarigan (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2010)
Pesanggrahan river with total extent of watershed about 13,384 ha is one of rivers flowing through Jakarta City that causes flood problem every years. Many effort has been done to reduce flood problem, among others is to build reservoir in watershed, but the effectiveness of reservoir is still questionable. A research aimed to analyze gap of reservoir capacity changes and its influence on hydrological response and to arrange the scenario of reservoir capacity change to improve hydrological response in Pesanggrahan Watershed was done using HEC-HMS Model. Reservoir capacity change scenarios applied to the actual rainfall condition and designed rainfall condition with a certain recurrence interval. The scenarios consist of: reservoir with the exsisting condition (scenario 1), increase depth of reservoir to 5 meters (scenario 2) and build 6 reservoirs on Pesanggrahan watershed (scenario 3). The model was calibrated using daily discharge data from the date of January 10th to April 30th 2009. Model calibration result shows that model is quite accurate to predict peak discharge in Pesanggrahan Watershed with Nash-Sutcliffe efficiency value = 0.9817 and R2 =0.975. Simulation results showed that the reservoir is effective in decreasing its local effect to peak discharge (reservoir area). The presence of reservoir with existing condition reduce only 6.38 % of the peak run off in outlet Kebon jeruk, whereas building of 6 reservoir will reduce 24.6 % of the peak run off in outlet Kebon jeruk.Keywords : HEC-HMS Model, peak discharge, Reservoir capacity change